Training and Union Wages - Dustmann, Christian; Schönberg, Uta (The Review of Economics and Statistics, 2009)
This paper investigates whether unions, through imposing wage floors that lead to wage compression, increase on-the-job training. Our analysis focuses on Germany. Based on a model of unions and firm-financed training, we derive empirical implications regarding apprenticeship training intensity, layoffs, wage cuts, and wage compression in unionized and nonunionized firms. We test these implications using firm panel data matched with administrative employee data. We find support for the hypothesis that union recognition, via imposing minimum wages and wage compression, increases training in apprenticeship programs.